Pengaruh Pembelajaran Berbasis Budaya terhadap Motivasi Belajar Bahasa Mandarin: Studi Pustaka - Khairun Nisa; Widia Amelia Setiawan; Aida Hanifah Assyahidah; Mochamad Ramadhan Gunawan; Khalda Azizah; Asti Istriyani; Khashia Nashwa Kamila Dirgantoro (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Language is closely related to social and cultural aspects, including in the process of learning foreign languages such as Mandarin. Effective Chinese language learning does not only focus on linguistic aspects, but also requires an understanding of the culture of origin of the language. The purpose of this paper is to analyse the application of culture-based learning in increasing motivation to learn Chinese. The method used is literature study or library research, with documentation technique as data collection method and content analysis technique as data analysis method. Based on the analysis of twelve research articles, it was found that the integration of cultural elements such as traditional games, visual media, and Chinese pop culture can create a learning experience that is fun, interesting, and encourages students' curiosity towards Chinese. In conclusion, culture-based learning is proven to have a positive influence on motivation to learn Chinese and can be used as an alternative teaching strategy that is more contextual and fun.